Methylene Blue Degradation with Sulfonated SPG20 Silica-Fe₂O₃ Hybrid Photocatalysts - Ulfa, Maria; Salsabila, Pramesta Rosa; Saputro, Agung Nugroho Catur; Nurharyati, Nanik Dwi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
This study aims to synthesize and evaluate the photocatalytic performance of a modified mesoporous silica-based composite, Fe₂O₃/SPG₂₀–SO₃H, for methylene blue degradation. The catalyst was prepared via a soft-template method using P123 surfactant and gelatin as dual structure-directing agents. Characterization results confirmed the formation of Fe₂O₃ crystallites with a dominant size of 2.14 nm and crystallinity of 90.85%. FTIR spectra revealed the presence of –COOH, Si–O–Si, Si–OH, and –OH groups, while sulfonate-related bands (–SO₃H, O=S=O) were not observed in XRD patterns, suggesting amorphous or poorly crystalline sulfonic groups. SEM analysis indicated rod-like catalyst morphology. Photocatalytic testing under various temperatures showed that Fe₂O₃/SPG₂₀–SO₃H achieved the highest degradation efficiency at 70 °C, maintaining over 92.14 % efficiency for up to 120 minutes of contact time. Lower temperatures (5 °C and 15 °C) led to reduced and less stable degradation activity. These results indicate that both sulfonation and iron oxide impregnation, combined with optimal operating temperature, significantly enhance the photocatalytic performance of mesoporous silica systems, offering a cost-effective and environmentally friendly solution for dye-contaminated wastewater treatment. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).